2021
DOI: 10.21203/rs.3.rs-182859/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Plasma Peptides of Alzheimer’s Disease

Abstract: BackgroundA practical strategy to discover proteins specific to Alzheimer’s dementia (AD) may be to compare the plasma peptides and proteins from patients with dementia to normal controls and patients with neurological conditions like multiple sclerosis or other diseases. The aim was a proof of principle for a method to discover proteins and/or peptides of plasma that show greater observation frequency and/or precursor intensity in AD. The endogenous tryptic peptides of Alzheimer’s were compared to normals, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 120 publications
(204 reference statements)
0
2
0
Order By: Relevance
“…FBXL3 and ASB4 are closely associated with circadian rhythms [37,38]. RNF144B [39], UBR1 [40], and UBE2G1 [41] play important roles in psychiatric disorders and neurodevelopmental diseases.…”
Section: Discussionmentioning
confidence: 99%
“…FBXL3 and ASB4 are closely associated with circadian rhythms [37,38]. RNF144B [39], UBR1 [40], and UBE2G1 [41] play important roles in psychiatric disorders and neurodevelopmental diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In this table, we find 13 genes with AD-related literature records, 5 genes with ADrelated records of the DisGeNet database (APOE, TF, PSEN1, MTHFR and MAOB), and 7 genes with AD-related records in literature while not in DisGeNet (EIF4G1, SNCA, SNCB, MAOA, MTHFD1, CP, AOC3). For example, Florentinus-Mefailoski showed that the increase of mean precursor strength of peptides from several plasma proteins (such as EIF4G1) was related to AD [76]. Bergström observed the increased levels of synuclein beta (SNCB) in cerebrospinal fluid (CSF) from AD samples compared with controls [77].…”
Section: Case Studiesmentioning
confidence: 99%